Investigation on Structural Behaviors of Precast Lightweight Foamed Concrete Sandwich Panel (PLFP) Using Finite Element Method - Lim, Heng Hoo; Tajul Ariffin, Ahmad Mubarak (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Development of Precast Lightweight Foamed Concrete Sandwich Panel (PLFP) has achieved global with Industrial Building System (IBS). PLFP assists reduction in multiple loads and longer spans. Recently, focused on reduced concrete thickness and prioritize textile reinforced concrete. This study has objectives to design different PLFP models with different polystyrene thickness to overall thickness in 500 mm width and 1000 mm length. The study also analyses structural behaviors in term of maximum equivalent elastic strain, maximum equivalent stress, total deformation and maximum deformation. The results include evaluation of steel reinforcement ratio, body mass, and presence of fatigue and fracture of different PLFP. Finite element method (FEM) using ANSYS software with Explicit Dynamics to investigate structural bahavior of PLFP under compression test, 3- point bending test, and tensile test. PLFP constructed in 1:3 scale with two pre-mixed 35 MPa concrete wythes and polystyrene insulation layer with thickness from 20 mm to 30 mm wythes. Reinforcement such as continuous shear truss, continuous trapezoidal-shaped, honeycomb and no reinforcement with AISI 4340 steels are applied. Results analysis found that steel reinforcement ratios of reinforced PLFP models from 1.9935% to 3.2284%. Based results, as the stress increases, the strain will increase. The PLFP with continuous shear truss reinforcement shows the least presence of fatigue and fractures compared to other designs. Therefore, it is concluded that PLFP with continuous shear truss reinforcement is the most suitable model, and can be applicable and safe for construction. A full-scale and different mechanical testing also recommended for further work.